Predictive Factors of Mortality in Acute Amphetamine Type Stimulants Poisoning; a Review of 226 Cases - Rahimi, Mitra; Lookzadeh, Somaieh; Sadeghi, Roxana; Soltaninejad, Kambiz; Shadnia, Shahin; Pajoumand, Abdolkarim; Hassanian-Moghaddam, Hossein; Zamani, Nasim; Latifi-Pour, Masoud (Archives of Academic Emergency Medicine, 2018)
Introduction: Amphetamine type stimulants (ATS) such as amphetamine and methamphetamine (MA) are one of the most important causes of poisoning in the world. In this study we aimed to define the predictive factors of mortality in acute ATS poisoning patients. Methods: This is a retrospective cross-sectional study on all cases with acute ATS poisoning who were referred to a referral center for poisoning, Tehran, Iran, from April 2011 to March 2014. Using patients’ medical records, demographic data, route of exposure, type and amount of ATS, the cause of poisoning, clinical presentations, and electrocardiogram (ECG) and laboratory findings, as well as patient’s outcomes were collected and analyzed regarding the independent predictive factors of mortality. Results: 226 cases with the mean age of 32.9 ± 10.9 years were studied (77% male). MA was the most abused ATS (97.4%) and the most frequent route of exposure was oral (55.3%). The mortality rate was 5.4%. There was a significant association between agitation (p = 0.002), seizure (p = 0.001), loss of consciousness (p < 0.001), creatine phosphokinase level (p = 0.002), serum pH (p = 0.002), serum HCO3 (p = 0.02), and PCO2 (p = 0.01) with mortality. However, serum HCO3 [OR=1.27 (95% CI: 1.07-1.50); p value=0.005], PCO2 [OR=0.89 (95% CI: 0.84-0.96); p value=0.002], and loss of consciousness [OR=0.019 (95% CI: 0.003-0.106); p value=0.000] were the only independent predictive factors of mortality. Conclusion: PCO2 ≥ 51 mmHg, serum bicarbonate ≤ 22.6 mEq/L, and loss of consciousness on admission could be considered as prognostic factors of mortality in acute ATS poisoning cases presenting to emergency department.